Relationship Between Dental Arch and Vertical Facial Morphology on Deutero-Malays Population - Christnawati, Christnawati; Karunia, Dyah (The Indonesian Journal of Dental Research)
Introduction: Vertical facial morphology characterized by steepness on mandibular plane (MP-SN) is an important variable in determining orthodontic diagnosis and treatment plan. Subjects with steepest mandibular plane angle tend to have larger teeth and narrower dental arch. The purpose of this study was to determine the relationship between dental arch and vertical facial morphology on Deutero-Malays population. Materials and Methods: Lateral cephalograms were obtained from 50 subjects. Inclusion criteria of subjects were including: 1) at least two original generation of Deutero-Malays; 2) never or not under orthodontic and orthognathic treatment; 3) having Class I Angle first molar relationship; 4) having full dentition except third molars; 5) showing regular or mild degree of irregularity according to Mal-alignment Index (Mal I); 6) no cups or interproximal caries; 7) overjet 2-4 mm; and 8) overbite 1/3 incisally lower incisor teeth. Vertical facial morphology was measured by determining steepness of mandibular plane (MP-SN) on lateral cephalogram using DBSWIN program. The measurement of dental arch perimeter length and width was conducted. Collected data was tabulated and analysed using correlation test. Result: The results of this study showed no significant correlation between steepness of mandibular plane and dental arch perimeter length and width on upper and lower arch. Conclusion: In conclusion, there was no relationship between vertical facial morphology and dental arch perimeter length as well as dental arch width on upper and lower arch.